Asymmetry in Dual Language Practice - Amrein, Audrey; Peña, Robert A. (Education Policy Analysis Archives, 2000)
The capacity for dual-language programs to deliver specific benefits to students with different primary and secondary language skills continues to be debated. Individuals favoring dual language assert that as it relies upon a reciprocal approach, dual language students acquire dual language proficiency without the need for teachers to translate from one language to another. By utilizing and conserving the language skills that students bring, dual language students also gain cross-cultural understandings and an expanded opportunity to realize academic success in the future. Research that explores whether these programs meet the needs of monolingual and bilingual students is limited. The intent of this study is not to criticize dual language practice. Instead, it is to describe a newly implemented dual language immersion program that exists and operates in Phoenix, Arizona. In particular, this study examines the practices of dual language teachers at Leigh Elementary School and the challenges encountered as school personnel worked to provide students with different primary and secondary language skills increased opportunities to learn.